Vaccination with formulation of nanoparticles loaded with Leishmania amazonensis antigens confers protection against experimental visceral Leishmaniasis in hamster - Maia Gonçalves, Ana Alice (2023)
Visceral leishmaniasis (VL) is a fatal disease caused by the protozoa Leishmania infantum for which dogs are the main reservoirs. A vaccine against canine visceral leishmaniasis (CVL) could be an important tool in the control of human and CVL by reducing the infection pressure of L. infantum. Despite the CVL vaccine available on the market, the Brazilian Ministry of Health did not implement the use of it in their control programs. In this sense, there is an urgent need to develop more efficient vaccines. In this study, the association between two polymeric nanoformulations, (poly (D, L-lactic) acid (PLA) polymer) loading Leishmania amazonensis antigens, was evaluated as a potential immunobiological agent against VL using golden hamsters as an experimental model. The results indicated that no significant adverse reactions were observed in animals vaccinated with LAPSmP. LAPSmP presented similar levels of total anti-Leishmania IgG as compared to LAPSmG. The LAPSmP and LAPSmG groups showed an intense reduction in liver and spleen parasitic load by qPCR. The LAPSmP and LAPSmG vaccines showed exceptional results, indicating that they may be promising candidates as a VL vaccine.